1987
DOI: 10.1172/jci113119
|View full text |Cite
|
Sign up to set email alerts
|

B cell insensitivity in a rat model of non-insulin-dependent diabetes. Evidence for a rapidly reversible effect of previous hyperglycemia.

Abstract: In perfused pancreas of rats rendered diabetic by streptozotocin injection (STZ) during neonatal age the insulin response to 27 mM glucose was significant but impaired. It was unaffected by the alpha adrenergic blocker phentolamine. When 27 mM mannoheptulose was added simultaneously with 27 mM glucose, insulin release was inhibited, but less promptly than in pancreases from non-diabetic rats. When mannoheptulose was introduced 15 min after starting perfusion with 27 mM glucose, inhibition was apparent in non-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
25
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 35 publications
7
25
0
1
Order By: Relevance
“…In contrast, perfusate containing 5.5 mmol/1 glucose (well below the normal plasma glucose value in rats) failed to achieve the same effect, indicating that the return of glucose-induced insulin secretion was not simply an effect of removing hyperglycaemia but instead depended on the absence (or possibly extremely low level) of glucose. The same observation has been made in other hyperglycaemic rodent models [15,22,23] suggesting that rapid restoration of glucose responsiveness in the presence of profound glucopoenia is a fundamental characteristic of hyperglycaemia-associated Beta-cell dysfunction. Some aspects of these findings need to be emphasized.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In contrast, perfusate containing 5.5 mmol/1 glucose (well below the normal plasma glucose value in rats) failed to achieve the same effect, indicating that the return of glucose-induced insulin secretion was not simply an effect of removing hyperglycaemia but instead depended on the absence (or possibly extremely low level) of glucose. The same observation has been made in other hyperglycaemic rodent models [15,22,23] suggesting that rapid restoration of glucose responsiveness in the presence of profound glucopoenia is a fundamental characteristic of hyperglycaemia-associated Beta-cell dysfunction. Some aspects of these findings need to be emphasized.…”
Section: Discussionsupporting
confidence: 71%
“…Animal models should theoretically provide a way to investigate this question, but reversal studies in hyperglycaemic rat models have provided conflicting results. Using in vitro techniques, glucose-induced insulin secretion has been restored in as little as 40 min [15]. In contrast, in vivo insulin injections have proved to be of varying success and require days to work [16][17][18].…”
mentioning
confidence: 99%
“…However, the basic features are well worth presenting because the insights gained from investigations on glucose desensitization are also shaping the lines of thought in investigations of the desensisitization by nonnutrient, pharmacological insulin secretagogues. The main feature that distinguishes glucose desensitization from glucose toxicity is the reversibility of the diminished secretory responsiveness (8). This reversibility can be suprisingly rapid: it was described to occur in vitro within minutes after changing from a moderately elevated glucose concentration back to a nonstimulatory concentration (9).…”
Section: Glucose Desensitization: Concepts and Controversiesmentioning
confidence: 99%
“…14) Other authors confirmed these findings and showed that neonatally-STZ treated rats in adulthood display some of the typical characteristics of diabetes. [15][16][17][18] We demonstrated in a previous study that responses of mesenteric microvessels of n-STZ diabetic rats to endothelium-dependent vasodilator acetylcholine and to sodium nitroprusside, an endothelium-independent vasodilator, were significantly reduced compared with non-diabetic rats. We concluded that the impaired vasodilatation is, in part, due to a reduced sensitivity of vessels to NO and to a reduced production and/or bioavailability of NO.…”
mentioning
confidence: 86%